Impact of the use of complete dentures on the quality of life of institutionalized elderly people - Ana Beatriz Franco Fernandes; André Vivan Garcia; Brenda Procopiak Gugelmin; Cibele de Almeida Kintopp; Eduardo Pizzatto; Maria Ângela Naval Machado; Marilisa Carneiro Leão Gabardo (Editorial Ciencias Médicas, 2020)
Introduction: The use of complete dentures has an impact on oral health-related quality of life. Elderly people are the population sector to be researched into from this perspective. Objective: Evaluate the self-perception of the impact of the use of complete dentures on the oral health-related quality of life of institutionalized elderly people. Methods: The study sample was 20 elderly people from Lar dos Idosos Recanto do Tarumã, Curitiba, Paraná, Brazil. Evaluation of demographic and economic details, habits and clinical aspects was based on the information collected with the Geriatric Oral Health Assessment Index questionnaire. The data were subjected to descriptive and bivariate analysis (Chi-squared test), with a significance of 5%. Results: Mean age was 75.2 (SD = 8.8) years and mean time of denture use was 27.9 (SD = 18.5) years. Income was below minimum wage in 80.0% of the participants, whereas the last visit to the dentist had occurred more than a year ago in 70.0%. The worst reports had to do with chewing, represented by problems to chew food and discomfort when eating, with 25% positive answers to each question. The sum of the frequencies of the answers "sometimes" and "always" about dissatisfaction with or unhappiness about the appearance of the mouth was reported by 60% of the respondents. Unsatisfactory retention of the lower denture occurred in 50.0% of the cases, whereas occlusion problems were present in half of the sample. Defects were present in 70.0% of the upper dentures and 45.0% of the lower dentures. No significant association (p> 0.05) was found between independent variables and outcome. Conclusions: The elderly people evaluated, regardless of the conditions of their complete dentures, reported satisfactory oral health-related quality of life.